Rewriting the History of Subject English through the Lens of 'Literary Sociability' - Doecke, Brenton (Changing English, 2019)
This essay offers readings of three significant texts within the history of subject English: The Teaching of English in England (1921), The Education of the Poetic Spirit (1949), and Growth Through English (1967). These texts each yield valuable insights into what students and their teachers can learn through their exchanges with one another within the social space of the classroom, especially the conversations that centre on the reading and writing they do together. Those insights, however, become more readily available to us if we resist accepted accounts of the history of subject English and attempt to read these texts anew. All three texts provide important intellectual resources in the struggle against neoliberal tendencies in educational thinking. The very attempt to engage in a responsive and nuanced dialogue with them over the historical divide that separates us constitutes a significant form of resistance to the instrumentalist thinking that characterises neoliberal ideology.